Strategic Use Cases of Digital Transformation Implementation in Cities in Developing Countries - Junaidi, Wendy (Bina Nusantara University, 2024)
Global competition for business process efficiencies and investment, rapidly growing and aging populations, rising concerns about climate change, economic inequality, digital gap, and keeping pace with technological innovation are just a few of the challenges cities around the world face in meeting citizens’ expectations for personalized, mobile government services. To address these complex systemic challenges, cities must design smart city initiatives as part of digital transformation implementation to connect disparate operations and siloed processes, starting with smaller, focused projects at the department level and progressing, step by step, toward an integrated city ecosystem. The purpose of this research is to provide insights into some strategic use cases for implementing digital transformation in cities in developing countries as a reference for prioritization so that local governments in developing countries can manage the complexities of smart city implementation through the empowerment of internet of things (IoT) technology. This research focused on some smart city use cases found in developing countries, i.e. Pune (India), Da Nang (Vietnam), and Mexico City (Mexico).